2019
DOI: 10.1186/s12913-019-3912-9
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-methods evaluation of mental healthcare integration into tuberculosis and maternal-child healthcare services of four South African districts

Abstract: BackgroundThe South African National Mental Health Policy Framework and Strategic Plan 2013–2020 was adopted to address the country’s substantial burden and inadequate treatment of mental illness. It outlines measures toward the goal of full integration of mental health services into primary care by 2020. To evaluate progress and challenges in implementation, we conducted a mixed-methods assessment of mental health service provision in tuberculosis and maternal-child healthcare services of four districts in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…In addition, in this study, HCs were less likely than hospitals to have screening tools and a focal/resource person for mental health. This finding is consistent with a previous study in South Africa, where less than half of nurses reported using a specific screening tool for mental disorders (Lovero et al., 2019). These findings imply that emphasis should be placed not only on screening women for IPV‐related mental disorders (Holden et al., 2012), but also on ensuring that the appropriate screening tools are available in health facilities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in this study, HCs were less likely than hospitals to have screening tools and a focal/resource person for mental health. This finding is consistent with a previous study in South Africa, where less than half of nurses reported using a specific screening tool for mental disorders (Lovero et al., 2019). These findings imply that emphasis should be placed not only on screening women for IPV‐related mental disorders (Holden et al., 2012), but also on ensuring that the appropriate screening tools are available in health facilities.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study in Malawi reported that healthcare providers felt inadequately prepared to handle the psychosocial and mental health consequences of IPV (Chepuka et al., 2014). In view of our findings and those of previous research, increased efforts should be directed towards improving the IPV‐related mental healthcare provided by nurses and midwives in health facilities by addressing both individual and facility‐related factors (Lovero et al., 2019).…”
Section: Discussionmentioning
confidence: 61%
“…The need for such a platform is further emphasised in the cross-sectional study by Araia and colleagues in Eritrea, which points out the shared risk factors such as BMI for the development of TB and DM whereby only 54.5% of the patients in the study were aware that they have both conditions [ 56 ]. Furthermore, free screening using mobile units was deemed effective to reach participants in rural areas where screening for diabetes was performed using handheld glucometers and screening for hypertension performed with electronic sphygmomanometers [ 57 ]. Provision of trained staff for the integrated screening and referral processes and coordination between the involved healthcare facilities was recognised as a facilitator for the success of this model [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Task-shifting, or the use of non-physician cadres (nurses, community health workers) to provide care, has been one approach recommended in LMICs to address clinical workforce shortages. Several recent studies have assessed the feasibility, pilot effectiveness, and cost-effectiveness of task-shifting in delivering integrated primary care in SSA, both for PLHIV [56,[67][68][69][70][71][72][73][74] and HIV-negative patients [75][76][77][78][79][80]. This growing literature highlights a few key recommendations for implementation.…”
Section: Integrated Service Deliverymentioning
confidence: 99%